POTENSI ANTIOKSIDAN GEL DAN DAUN KACAPIRING (Gardenia jasminoides Ellis) - Widnyana Yoga, IB Ketut; Andarwulan, Nuri; Prangdimurti, Endang (Prosiding Seminar Nasional MIPA, 2011)
Abstract: Leaf of kacapiring (Gardenia jasminoides Ellis) is a part of plant which is having component that can form gel. It has chlorophyll pigment and phenolic compound. The aims of this research were to identificate bioactive compound in leaves and gel which has antioxidant potency. Chlorophyll total was analyzed by spectrophotometer and its derivations of aceton extract (99.9%) by thin layer chromatography (TLC), meanwhile phenolic total and antioxidant capacity were analyzed by spectrophotometer. The result showed that bioactive component of kacapiring leaves and gel were chlorophyll total of 4926.25+190.31 and 1166.86+8.73Â mgKg-1db. Both of them had 5 fractions by acetone extract, i.e. chlorophyll a, chlorophyll b, lutein (chlorophyll derivates), feofitine and carotene. Phenolic total in leaves and gel contained 5215.91+2.97 and 2648.16+56.22 GAE/g db, and antioxidant capacity had 1.5 x 10-1+0.00 and 3.1x10-3 +0.00 mM TEAC/mg dw respectively